The economics of civil and common law - Madjd-Sadjadi, Zagros, 1968-, (Economics collection., 2016)
Law is supposed to encourage innovation, morality, and conformity with societal expectations, yet it may provide perverse incentives causing individuals, or even the State, to act in discordant, inefficient, and even immoral ways. It will explore the inefficiencies that are created that serve to deny individuals work and shelter in a haphazard and capricious manner. It will examine property rights, including eminent domain that lets the State take property away with seemingly arbitrary compensation to the owner. Individuals must understand both civil law, codified by statutes, and common law, enshrined in precedential judicial decisions, and why the common law tends to better reduce transactions costs and thus avoid courts entirely. This book is written for economists and noneconomists and has an extensive glossary of economic, political, and legal terms. Two items that are not formally treated in other economics of law textbooks are the legal organization of businesses and tax law from an economics perspective.